Desenvolvimento regional: um estudo baseado no crescimento econômico do município de Aparecida de Goiânia - Melo, Nelia Paula de (2015)
Based on the changes in obeserved economic terms in Aparecida de Goiania, a city located in the state of Goias, and inserted in the Metropolitan Region of Goiânia - RMG, this paper aims to present its development. As a reflection of the ideas coming from the regional development specialists, and in the light of this theoretical production, these seek support. The performance analysis is based on the economic and fiscal indicators local, able and necessary to identify the growth, and the notorious increase in business activities, in particular service providers, due to the high amount that come with settling. These facts provide the scenario in many faces add essential values, either by participation in the productive processes, the generation of employment and income to society. Facts which, although not lend a priority emphasis to the issue of development of the region causes heating of the local economy and awakens the interest for new developments, and makes it relevant to change the orientation of public policies that overcome, shall revise the old models, and still outweigh in a limited way, regional inequalities.